2021
DOI: 10.1097/md.0000000000025626
|View full text |Cite
|
Sign up to set email alerts
|

Presentation and management of nasal foreign bodies in a Chinese metro area

Abstract: Nasal foreign bodies in children are common complaints encountered by pediatric otolaryngologists. We investigated clinical features, diagnosis, and treatment of nasal foreign bodies in children in a Chinese metro area. Six hundred sixty eight children with nasal foreign bodies presented to Shenzhen Children's Hospital, diagnosed and treated by the authors were enrolled from January 2016 to October 2019, causes for medical consultation, age, sex, duration, types, locations, removal, and complication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
2
3
0
Order By: Relevance
“…When we divided the nasal FBs into organic and inorganic materials, the most common nasal FBs were inorganic compounds, accounting for 73.3% of the extracted objects. This finding was consistent with those of previous reports [ 5 , 7 , 9 ]. The most common shape of nasal FBs was round-shaped objects (58.5%), such as beads, beans, fruit seeds, and nuts.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…When we divided the nasal FBs into organic and inorganic materials, the most common nasal FBs were inorganic compounds, accounting for 73.3% of the extracted objects. This finding was consistent with those of previous reports [ 5 , 7 , 9 ]. The most common shape of nasal FBs was round-shaped objects (58.5%), such as beads, beans, fruit seeds, and nuts.…”
Section: Discussionsupporting
confidence: 94%
“…This study demonstrated a higher frequency (63.7%) of a nasal FB in patients aged 2–4 years, which was in line with previous studies [ 4 , 5 , 9 , 11 ]. The incidence of nasal FBs decreased dramatically after the age of 6 years.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Nasal foreign bodies have been widely reported in the otorhinolaryngology (ORL) literature with unilateral nasal discharge in children aged 1-5 years being the most common presentation [ 1 ]. However, leech infestation in the nose causing unilateral epistaxis is rare and scarcely reported.…”
Section: Introductionmentioning
confidence: 99%
“…Foreign bodies offer a diagnostic challenge to clinicians, and nasal foreign bodies have the potential to lead to significant morbidity, such as dislocation, airway obstruction septal perforation, infection, and deep mucosal laceration [1,2]. It has been reported that nasal foreign bodies are more common in children than in adults, the right nasal cavity is the most common site, and common symptoms are nasal discomfort and nasal discharge [3]. The most common foreign bodies are various seeds, and plastic beads or buttons, batteries, stones, toy pieces, and food particles have also been reported to be common types [4].…”
Section: Introductionmentioning
confidence: 99%